Theognidea (księga druga) – próba określenia gatunku - Szczot, Monika (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The subject of the article is to identify and name types of lyrical poetry present in Corpus Theognideum. The direct lyrical poetry presented in this series focuses on confessions of the lyrical ‘I’, whose monologue adopts the form of an open confession addressed to a reader. This “dialogue opening” to a reader is, however, only a formal sign, a pretext demonstrating the emotional approach of the lyrical “I” to the world. The entire text is initiated by the lyrical expressions of the lyrical “I” and focuses on the speaker himself and his feelings.
Theognidea (book two) – an attempt to determine the genre
Keywords: diret lyrical poetry; dialogue; autopresentation